1991
DOI: 10.3109/00207459108985460
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced suppression of experimental allergic encephalomyelitis in the rat

Abstract: Numerous experiments have demonstrated that physical stress can alter immunological parameters. However, little attention has been paid to the interrelationship between stress and autoimmune processes. The present study was designed to determine the influence of electric shock and sound stress on the development of experimental allergic encephalomyelitis (EAE). Ten-week-old male DA rats highly susceptible to EAE were used. Rats were subjected to the stress procedure during 19 days either before or after immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Although the etiology of multiple sclerosis remains uncertain, epidemiological studies suggest that viral infection during adolescence may be an initiating factor in genetically susceptible individuals (Acheson 1977; Alter et al 1986; Hernan et al 2001; Kurtzke et al 1995; Sospedra and Martin 2005). Psychological stress has also been shown to have a profound impact on animal models of multiple sclerosis, such as Theiler's virus infection (Campbell et al 2001; Johnson et al 2004, 2006; Meagher et al 2007a, b; Mi et al 2004, 2006a, b; Sieve et al 2004, 2006; Steelman et al 2009; Welsh et al 2004; Young et al, in press) and Experimental Autoimmune Encephalomyelitis (EAE; Bukilica et al 1991; Dowdell et al 1999; Griffin and Whitacre 1990; Griffin et al 1993; Levine and Saltzman 1987; Levine et al 1962; Stephan et al 2002; Teunis et al 2002; Whitacre et al 1998). Although several studies have shown that early life stress can alter the course of EAE (Laban et al 1995a, b; Stephan et al 2002; Teunis et al 2002), the impact on Theiler's virus infection remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiology of multiple sclerosis remains uncertain, epidemiological studies suggest that viral infection during adolescence may be an initiating factor in genetically susceptible individuals (Acheson 1977; Alter et al 1986; Hernan et al 2001; Kurtzke et al 1995; Sospedra and Martin 2005). Psychological stress has also been shown to have a profound impact on animal models of multiple sclerosis, such as Theiler's virus infection (Campbell et al 2001; Johnson et al 2004, 2006; Meagher et al 2007a, b; Mi et al 2004, 2006a, b; Sieve et al 2004, 2006; Steelman et al 2009; Welsh et al 2004; Young et al, in press) and Experimental Autoimmune Encephalomyelitis (EAE; Bukilica et al 1991; Dowdell et al 1999; Griffin and Whitacre 1990; Griffin et al 1993; Levine and Saltzman 1987; Levine et al 1962; Stephan et al 2002; Teunis et al 2002; Whitacre et al 1998). Although several studies have shown that early life stress can alter the course of EAE (Laban et al 1995a, b; Stephan et al 2002; Teunis et al 2002), the impact on Theiler's virus infection remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…e. Experimental model of MS (Table 1): Several authors have observed that stress exacerbates the early viral infection (Campbell et al, 2001;Sieve et al, 2004) and the later demyelinating disease in Theiler's virus infection. However, this does not coincide with studies using EAE, which show no effect of stress prior to disease induction, and a suppression during disease induction (Bukilica et al, 1991;Dowdell et al, 1999;Griffin et al, 1993;Levine & Saltzman, 1987;Levine et al, 1962). The differences in how stress affects EAE and Theiler's virus infection may lie in their immunological mechanisms of demyelination and neuronal destruction.…”
Section: Stress and Multiple Sclerosismentioning
confidence: 69%
“…In contrast, if restraint stress is applied concurrent with infection, the disease is again exacerbated (Campbell et al, 2001;Sieve et al, 2004). Likewise, Bukilica et al (1991) indicated that whereas 19 daily sessions of inescapable tail-shock (80, 5 s, 1 mA) have no effect when administered prior to EAE induction, stressor exposure following EAE induction has a protective effect. Specifically, tail-shock reduces the incidence and duration of EAE, delays disease onset, and decreases the severity of clinical and histological symptoms.…”
Section: Stress and Multiple Sclerosismentioning
confidence: 99%
“…However, autoantigen immunization with adjuvant has been shown to induce tissue‐specific autoimmune disease in a disease‐specific background. For example, experimental autoimmune encephalomyelitis in mice can be induced by exposure to peptides, suggesting that both genetic and environmental stresses can induce autoimmune disease 6 , 7 , 8 . The environmental factors, which induce cell apoptosis, are considered one of the main causes of autoimmune disease.…”
mentioning
confidence: 99%